Modern Pedagogical Technologies in Teaching Religious Studies - Носирова Азиза Рустамовна (Scientific Trends, 2023)
Pedagogical technology aimed at providing a pre-designed and guaranteed result in the educational process, orienting a holistic process based on a certain sequence in teaching to achieve a goal based on the needs of the student, organizing training based on modular technology and forming concepts regarding the use of interactive methods in teaching religious studies.
Keywords: Module, Technology, Interactive, Passive, Active, Pedagogical Technology, Style, Motivation, Brainstorming, Comparison.